2011
DOI: 10.1007/s00705-011-0925-z
|View full text |Cite
|
Sign up to set email alerts
|

Feline leukemia virus outbreak in the critically endangered Iberian lynx (Lynx pardinus): high-throughput sequencing of envelope variable region A and experimental transmission

Abstract: The Iberian lynx is the most endangered felid species. During winter/spring 2006/7, a feline leukemia virus (FeLV) outbreak of unexpected virulence killed about 2/3 of the infected Iberian lynxes. All FeLV-positive animals were co-infected with feline hemoplasmas. To further characterize the Iberian lynx FeLV strain and evaluate its potential virulence, the FeLV envelope gene variable region A (VRA) mutant spectrum was analyzed using the Roche 454 sequencing technology, and an in vivo transmission study of lyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 82 publications
1
36
0
1
Order By: Relevance
“…Our group also reported a generalized immune depletion apparently unrelated to infectious agents or other systemic diseases after evaluating lymphoid tissues in a representative portion of the population during the years 1998-2003 (Peña et al, 2006). A feline leukemia virus infection outbreak in the Doñana National Park population of Iberian lynxes was reported during a six month period between 2006 and 2007 (Meli et al, 2010(Meli et al, , 2011. During this period, six animals died presumably due to the infection (Meli et al, 2011).…”
Section: Glomerular Injury In the Iberian Lynxmentioning
confidence: 61%
See 2 more Smart Citations
“…Our group also reported a generalized immune depletion apparently unrelated to infectious agents or other systemic diseases after evaluating lymphoid tissues in a representative portion of the population during the years 1998-2003 (Peña et al, 2006). A feline leukemia virus infection outbreak in the Doñana National Park population of Iberian lynxes was reported during a six month period between 2006 and 2007 (Meli et al, 2010(Meli et al, , 2011. During this period, six animals died presumably due to the infection (Meli et al, 2011).…”
Section: Glomerular Injury In the Iberian Lynxmentioning
confidence: 61%
“…During this period, six animals died presumably due to the infection (Meli et al, 2011). Sequence analysis revealed homology with a strain originally identified in domestic cats suggesting co-infection between species (Meli et al, 2011;Geret et al, 2011). Prior to this time, the reported prevalence of feline leukemia virus in the same population was relatively low (Luaces et al, 2008) and evidence of lesions or death directly associated with the viral infection was unknown.…”
Section: Glomerular Injury In the Iberian Lynxmentioning
confidence: 89%
See 1 more Smart Citation
“…Following the principle of the 3Rs (reduce, refine, replace), they were also part of another study that aimed to assess the diseaseinducing potential of the FeLV strain present in the Iberian lynx [13]. All of the animal experiments were performed according to the law and were officially approved by the veterinary office of the canton of Zurich (TVB 159/160/2010), as required by Swiss law.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The cats were also part of another study for which they were coinfected with FeLV; the details of the FeLV portion of this study were reported elsewhere [13]. Because coinfections with FeLV and feline hemoplasmas have been reported in domestic cats [14e16], and several studies even found an increased prevalence of FeLV infection in CMhm-infected cats [17e20], the chosen model mirrors the field situation.…”
Section: Introductionmentioning
confidence: 98%